2016
DOI: 10.1371/journal.pone.0165927
|View full text |Cite
|
Sign up to set email alerts
|

Two FgLEU2 Genes with Different Roles in Leucine Biosynthesis and Infection-Related Morphogenesis in Fusarium graminearum

Abstract: 3-isopropylmalate dehydrogenase (IPMD) encoded by LEU2 is a key enzyme in leucine (Leu) biosynthetic pathway. Analysis of the genome sequence of Fusarium graminearum revealed two paralogous LEU2 genes (designated as FgLEU2A and FgLEU2B) in this fungus and the deduced amino acid sequences of FgLeu2A and FgLeu2B share 45% identity. Targeted disruption of individual FgLEU2A/B gene in F. graminearum assigned a more crucial role of FgLeu2A in Leu biosynthesis as disruption of FgLEU2A resulted in mutant (ΔFgLeu2A-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…37 The reduction of leucine may be responsible for the regulation of some genes and proteins, for example, 2-isopropylmalate synthase (IPMS) and 3-isopropylmalate dehydrogenase (IPMD) that are generally inhibited by leucine. 38 IPMS and IPMD are the critical enzymes in leucine biosynthesis that catalyze the formation of 2-isopropylmalate from acetyl-CoA and 2-oxoisovalerate. 39 IPMS and IPMD did not change significantly at the gene level, indicating that the up-regulation of these two proteins was caused by the decrease of leucine.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The reduction of leucine may be responsible for the regulation of some genes and proteins, for example, 2-isopropylmalate synthase (IPMS) and 3-isopropylmalate dehydrogenase (IPMD) that are generally inhibited by leucine. 38 IPMS and IPMD are the critical enzymes in leucine biosynthesis that catalyze the formation of 2-isopropylmalate from acetyl-CoA and 2-oxoisovalerate. 39 IPMS and IPMD did not change significantly at the gene level, indicating that the up-regulation of these two proteins was caused by the decrease of leucine.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Leucine is not only a regulator of protein synthesis but also plays a vital role in regulating the signal transduction of the initiation of translation . The reduction of leucine may be responsible for the regulation of some genes and proteins, for example, 2-isopropylmalate synthase (IPMS) and 3-isopropylmalate dehydrogenase (IPMD) that are generally inhibited by leucine . IPMS and IPMD are the critical enzymes in leucine biosynthesis that catalyze the formation of 2-isopropylmalate from acetyl-CoA and 2-oxoisovalerate .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Studies of ketol-acid reductoisomerase ILV5 (10) and dihydroxy-acid dehydratase ILV3 (11) showed that they are crucial for BCAA biosynthesis, deoxynivalenol production, and full virulence of F. graminearum. Moreover, isopropylmalate dehydrogenase LEU2 (12) and isopropylmalate isomerase LEU1 (13), which catalyze the first two reactions of Leu biosynthesis, are both essential for fungal vegetative growth, conidiogenesis, and pathogenicity.…”
mentioning
confidence: 99%
“…FgLeu2A is crucial for leucine biosynthesis and fungal infection‐related morphogenesis. In contrast, a less important role of FgLeu2B in F. graminearum (Liu et al ., ). These indicated that further investigation need to be explored to study the functions of duplicated genes.…”
Section: Discussionmentioning
confidence: 97%